2010
DOI: 10.1007/s00018-010-0574-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Treg-like cells in Tetraodon: insight into the origin of regulatory T subsets during early vertebrate evolution

Abstract: CD4(+)CD25(+)Foxp3(+) regulatory T cells (Treg cells) are critical for the maintenance of peripheral tolerance, and the suppression of autoimmune diseases and even tumors. Although Treg cells are well characterized in humans, little is known regarding their existence or occurrence in ancient vertebrates. In the present study, we report on the molecular and functional characterization of a Treg-like subset with the phenotype CD4-2(+)CD25-like(+)Foxp3-like(+) from a pufferfish (Tetraodon nigroviridis) model. Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 42 publications
2
74
0
Order By: Relevance
“…Recombinant proteins of zebrafish CD80/86, CD83, and CD4 were prepared as previously described (31)(32)(33)(34). Briefly, sequences encoding these proteins were amplified with primers (Supplemental Table I) containing corresponding restriction sites at the 59-and the 39-ends.…”
Section: Production Of Recombinant Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant proteins of zebrafish CD80/86, CD83, and CD4 were prepared as previously described (31)(32)(33)(34). Briefly, sequences encoding these proteins were amplified with primers (Supplemental Table I) containing corresponding restriction sites at the 59-and the 39-ends.…”
Section: Production Of Recombinant Proteinsmentioning
confidence: 99%
“…Cellular viability was determined by trypan blue (0.4%) exclusion assay. For membrane IgM (mIgm) + B and CD4 + T cell separation, immunomagnetic sorting (MACS) was performed, as previously described (33). Briefly, lymphocytes were adjusted to ∼2 3 10 8 cells/ml.…”
Section: Cell Preparation and Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that TnIL-16 shares a number of similar characteristics with its mammalian counterpart in terms of gene organization, amino acid sequence, functional motifs or domains, molecular structure, protein cleavage site, and chemo- attractant function (29,75). Thus, IL-16 might be a highly conserved IL family member, which is conservative in both structure and function from fish to mammals throughout vertebrate evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive analysis of fish genomes and the EST database has only identified IL-15Ra like molecules in fish [37,62]. Both the trout and tetraodon IL-15Ra like molecules contain a signal peptide, a single sushi domain, a Pro/Thr rich region, a transmembrane domain and have a short intracellular tail as seen in IL-15Ra from mammals, birds and amphibians [60,62].…”
Section: Fish Il-2ra/il-15ramentioning
confidence: 97%